Antimicrobial Susceptibility and Microorganisms Isolated from Blood Cultures of Hospitalized Patients in Intensive Care Units - Emine Küçükateş; Nazmi Gültekin (Haseki Tıp Bülteni)
Aim: The aim of this study was to evaluate microorganism growth in blood cultures of hospitalized patients in our intensive care units and to determine appropriate antimicrobial agents for treatment. Methods: We retrospectively investigated the blood cultures obtained from the patients hospitalized in the Coronary and Surgical Intensive Care Units at the Institute of Cardiology, İstanbul University, between July 2013 and December 2014. All microorganisms were identified using the conventional methods. Results: A total of 1034 blood cultures were obtained from 324 patients. Microbial growth was detected in 174 (16.8%) blood cultures of 68 patients. Among all microbial growth, 113 (58.55%) were gram-positive bacteria, 69 (35.75%) were gram-negative rods and 11 (5.7%) were fungi. Staphylococcus aureus was the most frequent microorganism (48; 24.87%), followed by coagulasenegative Staphylococci (35; 18,13%), Enterococcus spp. (30; 15,54%), Stenotrophomonas maltophilia, Escherichia coli, and Pseudomonas spp. 60.4% of Staphylococcus aureus were methicillin-resistant and 65.7% of coagulase-negative Staphylococci were also methicillin-resistant. All Staphylococci and Enterococci were not resistant to vancomycin, teicoplanin and tigecycline. All the gram-negative rods were susceptible to colistin and tigecycline, followed by imipenem (71.6%) and meropenem (70.7%). Conclusions: We assume that infection control measures must be increased due to high antibiotic resistance and besides, antibiotic policies should be improved.